Advantages of Cubism and its implications in graphic design (Al-Academy, 2025)
Cubism, with its philosophical and technical character at the same time, is based on formal outcomes that are compatible with the paths of formal formations in design as one of the applied arts. The design process represents a movement of creative activity in the artistic field and what it embodies in meeting functional and performance needs according to visual discourses that include within them vocabulary and symbols that take a form. Varied relationships in producing a different style depending on cultural and social change, which are closely linked to change in time and development in technical fields.    The relationships that characterize the characteristics of the Cubist school are artistically reflected in the fields of graphic design through the formal constructivism of Cubism. It is also characterized as a method and direction that appears to be at a clear level of fundamental understanding of the development of contemporary concepts and ideas in the arts of design in general and graphic art in particular.